2006
DOI: 10.1002/pbc.20581
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C is a suitable marker for routine monitoring of renal function in pediatric cancer patients, especially of very young age

Abstract: CysC represents a suitable marker for monitoring renal function in pediatric cancer patients. In young children (<3 years), CysC may have a better diagnostic value than SCR. Future studies should show if CysC can improve renal monitoring by replacing SCR, especially in very young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
1
25
0
2
Order By: Relevance
“…Some studies have reported that cystatin C can be used as an appropriate marker in monitoring the renal function, especially in children. 16,18,23 In fact, accurate and simple GFR measurement is crucial in elderly cancer patients. The results from the studies regarding adults are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that cystatin C can be used as an appropriate marker in monitoring the renal function, especially in children. 16,18,23 In fact, accurate and simple GFR measurement is crucial in elderly cancer patients. The results from the studies regarding adults are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…According to Filler and Lepage [8] , eGFR based on the Schwartz formula tends to overestimate filtration function of kidney. Estimating GFR from serum concentrations of cystatin C seems to be more reliable, accurate and precise than from endogenous creatinine [5,9] . Furthermore, we used classic constants (W is either 0.55 for children aged 2-12 years and adolescent girls, or 0.7 for adolescent boys) [3] to assess eGFR by the Schwartz formula.…”
Section: Discussionmentioning
confidence: 99%
“…Cystatin C is also considered to be a suitable marker for monitoring renal function in children with neoplastic disease [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the use of serum CysC in assessing nephrotoxicity from drugs used to treat cancer, particularly cisplatin (134,254,255,259). Most of these have been performed in children, in whom measurement of urinary creatinine clearance is particularly difficult and all agree that serum cystatin is a far more sensitive marker than serum creatinine to detect reduced GFR or creatinine clearance after cisplatin administration.…”
Section: Cysc and Cancermentioning
confidence: 99%